Pengaruh latihan medicine ball dan latihan shoulder press terhadap kemampuan smash dalam permainan bulu tangkis - Hidayat, Taufiq; Munandar, Rizky Aris; Pratama, Sandi Achmad; Zulfikar, Iman (Universitas Hamzanwadi, 2024)
The purpose of the study was to examine the effect of medicine ball and shoulder press training on the strength of smash shots. This type of research is experimental. This research design is pretest-postest design. The population in this study were all men's badminton UKM STKIP Yapis Dompu 13 students. The sampling technique was purposive sampling. The instruments used in this study were medicine ball, the length of the throw of the medicine ball and shoulder press the number of times the ability to lift the shoulder press weight. The results of data analysis of group I pretest medicine ball averaged 164.05 joules and posttest averaged 174.75 joules. Group II shoulder press pretest average 29 kg for posttest average 31.69 kg. Experimental group I medicine ball t count = 6.236 > t table with sig = 0.000 there is an influence from the results of the experimental group I medicine ball. Group II shoulder press t count = 3.942 > t table with sig = 0.002 there is an influence on the pretest data and posttest results of the experimental group II shoulder press. Experimental group I experienced an increase after being treated with medicine ball training by 7% and group II with shoulder press training experienced an increase of 9%. It is concluded that shoulder press training than medicine ball training on the ability to hit smash.